Multicenter comprehensive methodological and technical analysis of 832 pressurized intraperitoneal aerosol chemotherapy (PIPAC) interventions performed in 349 patients for peritoneal carcinomatosis treatment: An international survey study. Issue 7 (July 2018) - Nowacki, Maciej; Alyami, Mohammad; Villeneuve, Laurent; Mercier, Frederic; Hubner, Martin; Willaert, Wouter; Ceelen, Wim; Reymond, Marc; Pezet, Denis; Arvieux, Catherine; Khomyakov, Vladimir; Lay, Laura; et al.
Abstract: Background: Pressurized intraperitoneal aerosol chemotherapy (PIPAC) is a new drug delivery method offered in selected patients suffering from non-resectable peritoneal carcinomatosis (PC). As reported experience is still limited, we conducted a survey among active PIPAC centers aiming to report their technical approach and clinical findings. Methods: An online survey was sent to active PIPAC centers worldwide. The questionnaire consisted of 34 closed questions and was conducted over a period of 3 months beginning in March 2017. Results: Nine out of 15 contacted centers completed the questionnaire totaling 832 PIPAC procedures in 349 patients. Most common indications for PIPAC were PC from gastric, ovarian and colorectal origin. The mean time between each PIPAC procedure was 6–8 weeks. Seven of nine (77.8%) centers evaluate the PCI at every PIPAC procedure. At least four tissue samples for histopathology analysis were retrieved in 5 (55.6%). All centers (100%) use the same chemotherapy protocol: oxaliplatin at a dosage of 92mg/m 2 for PC of colorectal origin and a combination of cisplatin and doxorubicin at a dosage of 7.5mg/m 2 and 1.5mg/m 2, respectively, for other types of PC. Eight centers (88.9%) perform routine radiological evaluation before first PIPAC and after third PIPAC. Conclusion: These data confirm that PIPAC procedures are homogeneously performed in established centers. Standardization of the procedure will facilitate future international multicenter prospective clinical trials.